Assessment and possible management practices of non-recyclable plastics in Bandung city, Indonesia - Ibrahim, Indradhi Faisal; Thammarat Koottatep; Ekbordin Winijkul; Tatchai Pussayanavin; Government of Japan (Pathum Thani, Thailand : Asian Institute of Technology, 2021)
Overcapacity is one of the most problems of disposal sites in Bandung. Currently, plastic waste is the second highest fraction in the waste composition, which landfill is the only final treatment. The presence of non-recyclable plastics is one of the reasons that plastic waste has low circularity. Non-recyclable plastic can be defined as any plastic that cannot be recycled by the current recycling practice in a specific area because of technological hindrances and poor management. The methodology of this study includes interviews, field observations, and material flow analysis by using the STAN tool and Waste Flow Diagram. Through the existing management of waste shown that around 67% of plastic non-recyclable plastic is ending up in an open environment or landfill. The key issues and challenges of non-recyclable plastics from each sector are insufficiencies of infrastructure & facility, low understanding & knowledge of plastic, lack of awareness and participation, plastic not design for recycling, data availability, waste segregation, lack of material substitution, price of recycled resin, and stock of recycled resin. Two different scenarios were proposed to predict non-recyclable plastic management in 2025, in which scenario 1 applies technology and innovative practice, while scenario 2 focuses on upstream policy for promoting a sustainable consumption lifestyle and green business. Digital collection, material recovery facility, co-processing (i.e., RDF), and plastic-to-bricks are the new management in scenario 1. On the other hand, scenario 2 promotes design-for-recycling, choice editing, and extended producer responsibility (EPR). As a result, scenario 1 can increase the amount of recyclability of plastic from 33% to 83%, while scenario 2 escalates from 33% to 64%.
A research study submitted in partial fulfillment of the requirements for the degree of Master in Marine Plastics Abatement
Research studies project report (M.) - Asian Institute of Technology, 2021
Keywords: Plastics -- Environmental aspects -- Indonesia -- Bandung; Plastic scrap -- Indonesia -- Bandung; Plastics industry and trade -- Management